Sudden Recanalization: A Game-Changing Factor in Endovascular Treatment of Large Vessel Occlusion Strokes. Issue 4 (April 2020) - García-Tornel, Álvaro; Rubiera, Marta; Requena, Manuel; Muchada, Marian; Pagola, Jorge; Rodriguez-Luna, David; Deck, Matias; Juega, Jesus; Rodríguez-Villatoro, Noelia; Boned, Sandra; Olivé-Gadea, Marta; Tomasello, Alejandro; et al.
Abstract : Background and Purpose—: First pass (FP) recanalization has been shown to be a predictor of favorable outcome in endovascular treatment of stroke. The reasons why FP recanalization leads to better outcome as compared with multiple passes (MP) are unknown. We aim to investigate the recanalization pattern and its relationship with outcome. Methods—: Six hundred nine consecutive patients underwent endovascular treatment. Recanalization was defined as modified Thrombolysis in Cerebral Infarction score 2B-3. Favorable outcome was defined as modified Rankin Scale score of 0 to 2 at 90 days. Sudden recanalization (SR) was considered when modified Thrombolysis in Cerebral Infarction score varied from 0-1 to 2B-3 in a single pass. Progressive recanalization (PR) was considered if modified Thrombolysis in Cerebral Infarction score 2A was achieved at an interim pass before achieving recanalization. Patients were also categorized as recanalizers at FP, MP, or nonrecanalizers. Results—: Five hundred nine (83.9%) patients achieved recanalization. SR was achieved in 378 (62.1%) patients; 280 (46%) were FP-SR, and 98 (16.1%) were MP-SR. MP-PR was achieved in 131 (21.5%) patients. Rates of favorable outcome were similar between patients with FP-SR (57.5%) and MP-SR (57.1%; odds ratio [OR], 0.9 [CI, 0.53–1.54]; P =0.7) but lower in MP-PR (29.8%; OR, 3.33 [CI, 1.71–5.63]; P <0.01). Patients with MP-PR had better outcome than nonrecanalizer (17%; OR, 2.93 [CI, 1.42–6.15]; P <0.01). In univariate analysis, both FP recanalization (OR, 1.91 [CI, 1.31–2.72]; P <0.01) and SR (OR, 3.19 [CI, 2.12–4.95]; P <0.01) were associated with favorable outcome. However multivariate analysis adjusting for FP recanalization showed that the only procedural predictor of favorable outcome was SR (OR, 3.12 [CI, 1.91–5.16]; P <0.01). Higher number of passes were associated with worse outcome in patients with recanalization (OR, 0.75 [CI, 0.66–0.85]; P <0.01) but not in those with SR (OR, 0.94 [CI, 0.59–1.61]; P =0.937). Conclusions—: SR strongly predicts favorable outcome in patients undergoing endovascular treatment, even after previous unsuccessful attempts. PR may reflect clot fragmentation and embolization due to more friable composition, leading to worse outcomes. Prospective studies with independent assessment of recanalization pattern should validate these results. Abstract : Supplemental Digital Content is available in the text.